(untitled) (Gilgameš, 2019)
The religious practices performed in Lazio, for Diane of Nemi, and for Mater Matuta at Satricum, are well known thanks to literary sources whose details are sufficient to reconstruct them. They teach us that these rituals were performed by a group of women to replay a particular scene in various stages that can be completed or corroborated by archeology, but they do not necessarily insist on the importance of their bodies, nor on the emotional ties existing between the various devotees. Yet this is one of the foundations of the practice, so that the expected result is positively realized. If they are palpable in one of the two rituals, they are barely mentioned in the second, which is why they will be the focus of all the attention in this article.